2020
DOI: 10.9734/jocamr/2020/v9i330145
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hyperglycaemic, Anti-dyslipidaemic and Hepatoprotective Effects of the Polyherbal Mixture Diarth in Alloxan-induced Diabetic Rats

Abstract: Aim: This study evaluates the anti-hyperglycaemic, anti-dyslipidaemic and hepatoprotective effects of the polyherbal mixture diarth, in alloxan-induced diabetic rats. Methodology: A total of 35 male Wistar albino rats weighing between 120-140 g were used for this study. Diabetes was induced by a single intraperitoneal injection of freshly prepared alloxan-monohydrate (140 mg/kg body weight). Fasting plasma glucose (FPG) was determined using the glucose oxidase method. Total Cholesterol (TC), Triglyceride… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In a similar study, ethanolic extract of Carica papaya leaves showed comparable anti-hyperglycaemic activity when administered alongside glibenclamide in alloxan-induced diabetic rats [16]. The results also agree with the works of Briggs et al [17], in which the combination therapy of glibenclamide and the polyherbal drug diarth significantly reduced glucose levels, and was more effective compared to glibenclamide administered alone, in alloxan-induced diabetic rats. S -Significant, asignificantly different from negative control, bsignificantly different versus positive control, Gli -Glibenclamide, Ruzu -Ruzu Bitters ALT levels were significantly higher (P< .05) in the diabetic control and treatment groups, compared to the negative control, except for Group 3 (glibenclamide) which showed no significant difference (P> .05).…”
Section: Resultssupporting
confidence: 87%
“…In a similar study, ethanolic extract of Carica papaya leaves showed comparable anti-hyperglycaemic activity when administered alongside glibenclamide in alloxan-induced diabetic rats [16]. The results also agree with the works of Briggs et al [17], in which the combination therapy of glibenclamide and the polyherbal drug diarth significantly reduced glucose levels, and was more effective compared to glibenclamide administered alone, in alloxan-induced diabetic rats. S -Significant, asignificantly different from negative control, bsignificantly different versus positive control, Gli -Glibenclamide, Ruzu -Ruzu Bitters ALT levels were significantly higher (P< .05) in the diabetic control and treatment groups, compared to the negative control, except for Group 3 (glibenclamide) which showed no significant difference (P> .05).…”
Section: Resultssupporting
confidence: 87%
“…Poonam et al [22], reported that the combination therapy of garlic extract and metformin was more effective in reducing blood glucose levels, highlighting that garlic extract potentiates the hypoglycaemic effect of metformin. In a similar study, treatment with a polyherbal diarth and its combination treatment with glibenclamide were more effective than treatment with glibenclamide alone in reducing glucose levels to baseline control values [23].…”
Section: Resultsmentioning
confidence: 92%